Stratigraphy of Kendeng Zone in Miyono Village and Surrounding, Sekar District, Bojonegoro Regency, East Java, Indonesia - Mutawif Ilmi Muwaffiqih; Wahyu Ardiansyah Nugraha; Irvan Fatarwin Lubis; Mochammad Indra Novian (Geological Engineering Department Universitas Gadjah Mada, 2021)
This paper will comprehensively discuss the stratigraphy of the Kendeng Zone by using geological field mapping and laboratory analysis. The research area located in the Miyono Village and surrounding areas, Sekar District, Bojonegoro Regency, East Java with an area of 4x5 km2. Based on the geological mapping results obtained 160 points station with a variety of results in the form of tracking map of the research area. Laboratory analysis uses Embry and Klovan classification (1971), Pettijohn et al. (1987), and Mount (1985) for petrographic analysis, while paleontological analysis using Manual of Planktonic Foraminifera (Postuma, 1971) and Atlas of Benthic Foraminifera (Holbourn et al., 2013). This paper will show the differences between regional stratigraphy and the result, depositional environment, and its mechanism. Lithology units found grouping into nine units. The research area epoch ranged between N18-N23 (early Pliocene - Holocene) and the depositional environment from the lower bathyal to the terrestrial. The geological structures of the research area must be considered in the stratigraphic arrangement determination. Based on the analysis, the Kendeng Zone stratigraphic column was obtained and expected to provide accurate data of Kendeng Zone specifically around Miyono area.